6‐Methoxydihydrosanguinarine induces apoptosis and autophagy in breast cancer MCF‐7 cells by accumulating ROS to suppress the PI3K/AKT/mTOR signaling pathway. (18th September 2022) - Zhang, Lei; Zhang, Xinyue; Che, Delu; Zeng, Lizhong; Zhang, Yu; Nan, Kai; Zhang, Xinxin; Zhang, Hui; Guo, Zengjun
Abstract: 6‐Methoxydihydrosanguinarine (6‐MDS) is a natural benzophenanthridine alkaloid extracted from Hylomecon japonica (Thunb.) Prantl. It is the first time to explore the effect and mechanism of 6‐MDS in breast cancer. Network pharmacology, molecular docking, and molecular dynamics simulation technology were adopted to identify the potential targets and pathways of 6‐MDS in breast cancer. Besides, cell proliferation, apoptosis, and western blotting assays were conducted to investigate the effect of 6‐MDS on MCF‐7 cells. Network pharmacology, molecular docking, and molecular dynamics simulation results confirmed the effect of 6‐MDS on resisting breast cancer via the PI3K/AKT/mTOR signaling pathway. In addition, the functional experiments results demonstrated that 6‐MDS inhibited proliferation and induced apoptosis and autophagy. The autophagy inhibitor chloroquine and the silence of Atg5 augmented the effect of 6‐MDS on promoting apoptosis. Furthermore, 6‐MDS suppressed the PI3K/AKT/mTOR signaling pathway, and the PI3K inhibitor LY294002 enhanced these changes and promoted the 6‐MDS pro‐apoptotic and autophagy effects. 6‐MDS triggered the generation of reactive oxygen species. The pretreatment with antioxidant N‐acetyl‐L‐cysteine reversed the changes induced by 6‐MDS, including increases in apoptosis and autophagy and inhibition of the PI3K/AKT/mTOR pathway. In conclusion, 6‐MDS induces the apoptosis and autophagy of MCF‐7 cells by ROS accumulation to suppress the PI3K/AKT/mTOR signaling pathway.